INTENSI SWAMEDIKASI DI KALANGAN MASYARAKAT KECAMATAN UMBULHARJO YOGYAKARTA PADA MASA PANDEMI COVID-19: TINJAUAN THEORY OF PLANNED BEHAVIOR - De Karos, Vlorent Anggi; Widayati, Aris (Jurnal Kefarmasian Akfarindo, 2022)
Self-medication is the first and most common effort made by the community to overcome their health complaints. During the COVID-19 pandemic, 70% of patients with chronic diseases were absent from routine control and 12% missed the treatment process, increasing the mortality rate by 1.3%. Some of the impacts that occurred due to the impact of the COVID-19 pandemic on changes in health seeking became the basis for conducting this research. The purpose of this study was to determine the factors that contributed to the intention of self-medication among the community during the COVID 19 pandemic. The intention factor will be reviewed using the theoretical framework of Theory of Planned Behavior (TPB). This research is an analytic observational study with a cross sectional design. The sample was selected using the Cluster Sampling with a total sample of 144 respondents. Data analysis was carried out descriptively followed by multiple linear regression. The results of this study, the attitude (p value ≤ 0,05) and perceived behavioral control (p value ≤ 0,05) showed a partial contribution to self-medication intentions. While subjective norm (p value ≥ 0,05) partially has no effect on self-medication intentions. The construct of perceived behavioral control was the most contributing factor to the self-medication intention (β= 0,017). The results of the F test showed that attitude, subjective norm, and perceived behavioral control simultaneously contributed 26.4% to self-medication intentions (p value 0,05, F count > F table, R Square = 0.264). The results of this study can be used as consideration for the Yogyakarta Public Health Office in preparing a health promotion program related to good self-medication to the community.